Src mediates stimulation by vascular endothelial growth factor of the phosphorylation of focal adhesion kinase at tyrosine 861, and migration and anti-apoptosis in endothelial cells - Abu Ghazaleh, Robin; Kabir, Jahangir; Jia, Haiyan; Lobo, Mel; Zachary, Ian (Portland Press Ltd, 2001)
Vascular endothelial growth factor (VEGF) stimulates the tyrosine phosphorylation of focal adhesion kinase (FAK), increases focal adhesion formation and is chemotactic for human umbilical-vein endothelial cells (HUVECs). In the present study we identified the major sites of VEGF-induced FAK tyrosine phosphorylation and investigated the mechanism mediating this pathway in the action of VEGF. VEGF increased the focal adhesion localization of FAK phosphorylated at Tyr-397 (Y397) and Y861 but stimulated a marked increase in phosphorylation at Y861 without significantly affecting the total level of phospho-Y397 FAK. Inhibition of Src with the specific inhibitor 4-amino-5-(4-chlorophenyl)-7-(t-butyl)pyrazolo[3,4-d]pyrimidine (PP2) completely blocked VEGF-induced Y861 phosphorylation without decreasing the level of phospho-Y397 FAK. We also examined the role of Src in mediating endothelial functions of VEGF in which FAK has been implicated as having a role. PP2 markedly inhibited VEGF-induced chemotaxis and wound-healing cell migration. The Src inhibitor also decreased the anti-apoptotic effect of VEGF determined by surface staining of annexin V but did not increase FAK proteolysis or prevent the VEGF-dependent inhibition of FAK proteolysis. In contrast, the specific PtdIns 3-kinase inhibitor LY294002 induced apoptosis and markedly decreased p125(FAK) expression and increased FAK proteolysis but had little effect on Y861 phosphorylation. These findings identify Src-dependent FAK phosphorylation at Y861 as a novel VEGF-induced signalling pathway in endothelial cells and suggest that this pathway might be involved in the mechanisms mediating VEGF-induced endothelial cell migration and anti-apoptosis
Keywords: chemotaxis, endothelium, KDR, survival